Real-world evaluation of patiromer utilization and its effects on serum potassium in veterans with end stage kidney disease. Issue 50 (16th December 2022) - Pinnell, Derek; Patel, Shardool; Qualls, Joshua; Chen, Wei; Rathod, Anitha; Woods, Steven D.; Boutin, Slyvie; Kovesdy, Csaba P.; Tangri, Navdeep; Sauer, Brian C.
Abstract : Hyperkalemia (serum potassium [K+] ≥5.1) is life-threatening in patients diagnosed with end stage kidney disease (ESKD). Patiromer is approved for the treatment of hyperkalemia, although its role in hyperkalemic patients with ESKD is not well understood. This study describes real-world patiromer utilization in an ESKD population and its corresponding association with serum K+ level changes. The study population was comprised of US veterans with an outpatient dispensing of patiromer and 2 or more International Classification of Diseases diagnostic codes for ESKD. A treatment course of patiromer was defined by serial dispensing events without a 30-day gap. Patiromer utilization was described by duration, average dose, persistence, and proportion of days covered during patiromer course. Mean serum K+ values were described for baseline and 3 follow-up intervals during the 180-day follow-up period. There were 458 patients with ESKD included in the study. On average, patients had 1.24 (95% CI: 1.20–1.29) patiromer courses. Half of the population discontinued their first patiromer course within 30 days, while approximately 10% of patients remained persistent at the end of the 180-day period and 102 (22.3%) patients started a second course during the 180-day follow up period. Average serum K+ concentrations during baseline and the 3 evaluation intervals during the 180-day follow-up were 5.91 mEq/L (5.85–5.97), 4.94 mEq/L (4.86–5.03), 4.89 mEq/L (4.8–4.98) and 4.88 mEq/L (4.8–4.96). Few patients remained persistent on their initial course of patiromer at the end of follow-up, but approximately 20% of patients initiated a second treatment episode after a 30-day gap in treatment during the 180-day follow-up period. Nonetheless, average serum K+ in ESKD patients were sustainably reduced by approximately 1 mEq/L during follow-up.